KISAH LAKI-LAKI YANG MENIADA: TELAAH AKAR KATA DAN MAKNA MADAM DALAM TRADISI MIGRASI URANG BANJAR (THE TALE OF THE MAN WHO DISAPPEARED: STUDY OF ROOT WORD AND MEANING OF MADAM IN BANJARESE MIGRATION TRADITION) - Hakim, Arif Rahman (Universitas Lambung Mangkurat, 2024)
AbstractThe Tale of The Man Who Disappeared: Study of Root Word and Meaning of Madam in Banjarese Migration Tradition. This article examines the tradition of Banjarese migration called madam. The background of the article starts from the problem that there is no study on the Banjarese migration that focuses on discussing the etymology and meaning of madam. This issue indicates that the fundamentals in understanding the madam tradition have not been well developed. Based on this background, the purpose of this article is to conduct a comprehensive research on the study of the etimological root and the meaning of madam. The methodology in this study uses library research with a linguistic approach. The results of this study indicate that the word of madam has been written in the Hikayat Banjar with the word